Monetary Policy Transmission Mechanism in Gulf Cooperation Council Countries - Ziaei, Sayyed Mahdi (2010)
This study examines monetary policy transmission mechanisms in six members of (Persian) Gulf Cooperation Council (GCC). While GCC authorities had succeeded to maintain economic stability during 1980s and 1990s, in last decade they experienced economic fluctuation due to; the depreciation of US dollar (increasing imports cost), inflationary pressures (decreasing purchasing power), effects of foreign shocks, fix exchange rate problems, and consequences of worldwide economic crises. Two econometric methods namely structural vector autoregressive (SVAR) and panel vector autoregressive (PVAR) are used in this thesis. The results show that in GCC, the interest rate channel provides correct signs in accordance to theory, but the magnitude of effects is not very pronounced. A temporary rise in the short-term interest rate tends to be followed by a fall in output and price but these decreases aren’t amplitude. Moreover, in most GCC countries interest rate responds positively and simultaneously to unexpected positive innovation in the monetary aggregate (M2). Simultaneous interactions between monetary policy instruments and other variables such as monetary aggregate and exchange rate show that monetary policies would influence economy stronger if sovereignty of monetary authorities on monetary policy is increased. Furthermore, comparison between the channels of monetary policy in GCC countries indicate that there are two groups of countries classified in the matter of monetary policy transmission mechanisms; the first group includes; Saudi Arabia, the UAE and Bahrain. In this group the exchange rate channel is the most influential channel in the short term. The difference is that in long term in Saudi Arabia, the credit channel is the strongest channel after exchange rate channel, but in the UAE and Bahrain the interest rate channel is the most important channel. The second group includes; Kuwait, Oman and Qatar. In this group the credit channel is the strongest channel in the short term. However in the long term, the interest rate is strongest in Oman and exchange rate channel is most influential in the case of Kuwait and Qatar after credit channel. Moreover, effects of monetary policy on aggregate demand components demonstrate that (except Kuwait), monetary policy shocks influences investment more than other components of GDP. In conclusion, this study found that monetary policy transmission mechanism operate to some extent in the same underlying monetary pattern across the member of GCC countries, and with more flexible exchange rate and establishment of monetary union, influences of monetary policy on money and credit markets could be strengthened.